Biomaterials: Micro/Nano Dual‐Scale Crossed Sinusoidal Wavy Patterns for Synergistic Promotion of Proliferation and Endothelial Differentiation of Human Adipose‐Derived Stem Cells (Adv. Mater. Interfaces 10/2020). Issue 10 (20th May 2020) - Kim, Hyung Woo; Lee, Jeong Su; Park, Sung Jea; Rhie, Jong Won; Kim, Dong Sung
Abstract : The micro/nano dual‐scale crossed sinusoidal wavy patterns are fabricated to find out the cell behaviors of the human adipose‐derived stem cells (hASCs). Cell alignment, proliferation and endothelial differentiation of the hASCs are promoted on the particular micro/nano dual‐scale crossed sinusoidal wavy pattern. More details can be found in article number 1901983 by Dong Sung Kim and co‐workers.